Behavior and perceptions of hand hygiene practices among dental students - Costa, Eliana Dantas Da; Ambrosano, Glaucia Maria Bovi; Pinelli, Camila (Faculdade São Leopoldo Mandic, 2016)
ABSTRACTObjective: To investigate behavior and perception of hand hygiene practices among undergraduate students in a School of Dentistry.Methods: The study adopted a qualitative technique called Collective Subject Discourse (CSD). The sample comprised students enrolled in a Public School of Dentistry, in Sao Paulo State, Brazil (n=54). Semi-structured interviews were recorded in a digital voice recorder. Data analysis was carried out by means of a quali-quantitative approach with the help of Qualiquantisoft(r) software.Results: Students showed adequate knowledge regarding guidelines about hand hygiene practices. However, they considered their procedure gloves as an effective way to avoid crossed-infection, and mentioned inadequate infrastructure of sinks and sometimes lack of consumables undermined their adherence to hand hygiene practices. They reported health professionals and professors at the Institution as being reckless with handwashing, especially before donning gloves or after removal. Students reported the school properly guided them in relation to teaching hand hygiene practices, but they stated they were careless with the recommendations. Students were very concerned if they would hypothetically be treated by professionals who did not wash their hands.Conclusion: This study identified some of the hand hygiene compliance failures among dental students. Educational strategies by means of an increase in motivation to perform hand hygiene properly, and by adjusting professor's practices in front of the students would be crucial to improve adherence. Additionally, the improvement on the infrastructure in this institution by means of new washbasins and more available consumables would benefit hand hygiene adherence.

RESUMOObjetivo: Investigar o comportamento e a percepção sobre a prática da higiene das mãos entre acadêmicos de um Curso de Odontologia.Métodos: Este estudo adotou a técnica qualitativa Discurso do Sujeito Coletivo (DSC). A amostra foi composta por estudantes matriculados numa Faculdade Pública de Odontologia do Estado de São Paulo, Brasil (n=54). Entrevistas semiestruturadas foram registradas em um gravador digital. A análise dos dados foi realizada por meio de abordagem quali-quantitativa com auxílio do programa Qualiquantisoft(r).Resultados: Estudantes mostraram conhecimento adequado quanto às diretrizes sobre a prática de higiene das mãos. Porém, consideraram que as luvas de procedimento seriam efetivas para evitar a contaminação cruzada e afirmaram que a infraestrutura inadequada de pias e a falta de materiais de consumo minavam a adesão. Relataram que o comportamento em higiene das mãos de profissionais e de alguns professores era negligente quanto à higiene das mãos, especialmente antes de calçarem luvas e após retirarem. Relataram que a faculdade oferecia ensino para correto treinamento, mas atribuíram a si próprios a postura negligente. Entretanto, apresentaram-se muito preocupados de serem hipoteticamente atendidos por profissionais que não lavassem as mãos.Conclusão: Algumas falhas quanto à conformidade com a higiene das mãos entre estudantes de Odontologia foram identificadas. Estratégias educativas, por meio da motivação e do ajuste da conformidade da prática pelos professores seriam fundamentais para aumento da adesão. Adicionalmente, melhorias na infraestrutura nessa instituição, por meio de novas pias e disponibilidade irrestrita de material de consumo beneficiaria a adesão à higiene das mãos.
Comportamento e percepção de práticas de higiene das mãos entre os estudantes de Odontologia
Keywords: Behavior; Hand hygiene; Health human resource training; Qualitative research; Perception; Comportamento; Higiene das mãos; Capacitação de recursos humanos em Saúde; Pesquisa qualitativa; Percepção